Highly sensitive and selective LPG sensor based on alpha-Fe2O3 nanorods - Patil, Dewyani; Patil, Virendra; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
The alpha-Fe2O3 nanorods were successfully synthesized without any templates by calcining the alpha-FeOOH precursor in air at 300 degrees C for 2 h and their LPG sensing characteristics were investigated. The alpha-FeOOH precursor was prepared through a simple and low cost wet chemical route at low temperature (40 degrees C) using FeSO4 center dot 7H(2)O and CH3COONa as starting materials. The formation of alpha-FeOOH precursor and its topotactic transformation to alpha-Fe2O3 upon calcination was confirmed by X-ray diffraction measurement (XRD). X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis. The alpha-Fe2O3 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 1746-50 ppm LPG at 300 degrees C), extremely rapid response (similar to 3-4 s), relatively slow recovery (similar to 8-9 min), excellent repeatability, good selectivity and lower operating temperature (similar to 300 degrees C). Furthermore, the alpha-Fe2O3 nanorods are able to detect up to 5 ppm for LPG with reasonable response (similar to 15) at the operating temperature of 300 degrees C and they can be reliably used to monitor the concentration of LPG over the range (5-60 ppm). The experimental results clearly demonstrate the potential of using the alpha-Fe2O3 nanorods as sensing material in the fabrication of LPG sensors. Plausible LP G sensing mechanism of the alpha-Fe2O3 nanorods is also discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: alpha-Fe2O3 nanorods; FESEM; LPG sensor; Semiconductor gas sensors; TEM; XPS; XRD